Stalemate : Autonomy and Insurgency on the China-Myanmar Border - Ong, Andrew, 1983- (Book collections on Project MUSE., 2023)
"This book is an ethnographic account of political relations in an autonomous highland region in Myanmar, governed by the country's largest insurgent group, the United Wa State Army"--